Influencia del conocimiento de la educación ambiental en los extractores madereros de la provincia de Maynas – Loreto – 2024 - Rios Gil, Jodie Romy (2025)
The research was conducted using a qualitative approach, with a population of 261 holders of forest concessions granted since 2004 by the Regional Development Office of Loreto. The majority of the timber harvesters evaluated possess medium to high environmental skills, demonstrating significant potential for promoting sustainable management practices. Regarding environmental attitudes, it is evident that although most harvesters have a medium level of environmental skills, the high percentage with low practical skills constitutes a barrier to achieving sustainable forest management. It is urgent to implement field based environmental education programs, designed based on the sociocultural reality of the harvesters, to strengthen the necessary skills for the responsible use of forest resources. Improved environmental training not only reduces negative environmental impacts but also empowers harvesters as active agents in the conservation and rational use of forests. In particular, it is evident that harvesters with professional studies have higher scores in environmental education than those with only primary or secondary education. Environmental training will contribute not only to reducing negative environmental impacts but also to empowering harvesters as active agents in forest conservation and rational use.